2020
DOI: 10.1186/s11556-019-0234-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 9 weeks continuous vs. interval aerobic training on plasma BDNF levels, aerobic fitness, cognitive capacity and quality of life among seniors with mild to moderate Alzheimer’s disease: a randomized controlled trial

Abstract: Background: Evidence suggests that aerobic-type training confers physical benefits and appears to contribute positively to brain health. This study aims to compare the effect of 9-weeks continuous (CAT) to interval aerobic training (IAT) on brain derived neurotrophic factor (BDNF) plasma level, aerobic fitness, cognitive performance, and quality of life among senior with Alzheimer's disease (AD). Methods: 52 participants were randomly allocated into three groups (CAT n = 14; IAT n = 17; and Controls n = 21). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 94 publications
2
49
0
Order By: Relevance
“…However, 45% of the studies in mixed exercise did not show a positive effect of the intervention. Moreover, the least amount of exercise in all studies was 540 min ( 48 ), and the most were 7,800 min ( 54 ), and neither study found a significant cognitive improvement effect. Therefore, this means that the relationship between the amount of exercise and the effect of exercise is not clear.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…However, 45% of the studies in mixed exercise did not show a positive effect of the intervention. Moreover, the least amount of exercise in all studies was 540 min ( 48 ), and the most were 7,800 min ( 54 ), and neither study found a significant cognitive improvement effect. Therefore, this means that the relationship between the amount of exercise and the effect of exercise is not clear.…”
Section: Discussionmentioning
confidence: 78%
“…A total of twenty-two RCTs involving 1,647 AD participants (age 77.1 ± 6.3 years) were included in the study for review. The included studies were from sixteen countries, namely Brazil ( 16 , 45 , 47 ), France ( 18 , 46 , 48 ), USA ( 50 , 54 , 56 ), Italy ( 13 , 53 ), Nigeria ( 17 ), Netherlands ( 49 ), Denmark ( 11 ), Germany ( 15 ), Egypt ( 12 ), Finland ( 19 ), Iran ( 51 ), Albania & Spain ( 14 ), Sweden ( 52 ), Australia ( 20 ), and China ( 55 ). Participants were from the community, social centers, social clubs or individuals, memory clinics, or hospitals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that appropriate low-intensity exercise is more effective than highintensity exercise in protecting and restoring the aging brain in rats (Kim et al, 2003). In clinical trial cases, the results present a wide variation depending on the type and intensity of exercise (Enette et al, 2020). Thus, there are still many questions about the potential benefits of exercise in AD animal models and human patients.…”
Section: Perspectives For Future Studiesmentioning
confidence: 99%
“…Additional efforts have been achieved by using non-pharmacological approaches for treating mental illnesses, including phototherapy, nutritional supplements, and physical exercise [ 11 - 14 ]. In this regard, multiple findings have demonstrated that physical activity and exercise promote health benefits in patients with psychiatric disorders [ 15 - 18 ]. Exercise influences multiple neurobiological networks, including the endocannabinoid system [ 19 - 22 ], therefore, it is likely that this endogenous signaling arrangement might influence the effectiveness of exercise as a treatment for managing mental disorders.…”
Section: Introductionmentioning
confidence: 99%